Fluorescent Supramolecular Polymers Formed by Crown Ether-Based Host-Guest Interaction - Zhang, Jinjin; Qiu, Huayu; He, Tian; Li, Yang; Yin, Shouchun (Frontiers in Chemistry, 2020)
Inspired by the vast array of assemblies present in nature, supramolecular chemistry has attracted significant attention on account of its diverse supra-structures, which include micelles, vesicles, and fibers, in addition to its extensive applications in luminescent materials, sensors, bioimaging, and drug delivery over the past decades. Supramolecular polymers, which represent a combination of supramolecular chemistry and polymer science, are constructed by non-covalent interactions, such as host-guest interactions, hydrogen bonding, hydrophobic or hydrophilic interactions, metal-ligand interactions, π-π stacking, and electrostatic interactions. To date, numerous host-guest recognition systems have been reported, including crown ethers, cyclodextrins, calixarenes, cucurbituril, pillararenes, and other macrocyclic hosts. Among them, crown ethers, as the first generation of macrocyclic hosts, provide a promising and facile alternative route to supramolecular polymers. In addition, the incorporation of fluorophores into supramolecular polymers could endow them with multiple properties and functions, thereby presenting potential advantages in the context of smart materials. Thus, this review focuses on the fabrication strategies, interesting properties, and potential applications of fluorescent supramolecular polymers based on crown ethers. Typical examples are presented and discussed in terms of three different types of building blocks, namely covalently bonded low-molecular-weight compounds, polymers modified by hosts or guests, and supramolecular coordination complexes.